“Much, I am Sure, Depends on You”: James Fordyce’s Lessons on Female Happiness and Perfection - Bronk, Katarzyna (Studia Anglica Posnaniensia, 2013)
Conduct literature written for women has had a long tradition in British culture. According to scholars, such as Ingrid H. Tague (2002), it circulated most widely during the eighteenth century because new ideals of proper feminine behaviour and conduct developed. The Scottish Presbyterian minister and poet, James Fordyce (1720-1796), very observant of the transformations in his society as well as advocating the need to reform moral manners, likewise created a set of sermons dedicated to young women of the second half of the eighteenth century. He is worthy of close study not only because his Sermons to Young Women constitute an important yet understudied contribution to the tradition of conduct writing, but also because he records and disseminates opinions on female perfection both as a man of the church as well as the representative of his sex, thus presenting a broad scope of the official gender ideology of the eighteenth century. The proposed article engages in a close reading of Fordyce's rules and regulations pertaining to proper femininity, pointing also to the tone of his published sermon-manual and the socio-techniques used for the sake of perpetuating his ideological precepts for women. As such, the article is to prove that this popular eighteenth-century preacher, whose work was even mentioned on the pages of Jane Austen’s Pride and Prejudice, not only offers a significant contribution to ongoing research on conduct manual tradition as well as on feminist re-readings of women’s history, but also adds more evidence to feminist claims of a purposeful campaign aimed at creating a selfaware and self-vigilant woman who almost consciously strives to become the object of masculine desire, and allegedly all for her own good.